Electron-lattice interactions strongly renormalize the charge-transfer energy in the spin-chain cuprate Li2CuO2 - Steve Johnston (Nature Portfolio, 2016)
In transition metal oxides, an insulating band gap is found when the energy scales related to ionic charge excitations dominate over electronic itinerancy. Here, the authors demonstrate strong electron-phonon interactions in Li2CuO2and their effect on the insulating band gap.